PENGEMBANGAN E-MODUL GELOMBANG BUNYI BERBANTUAN APLIKASI PHYPHOX UNTUK MENINGKATKAN KEMANDIRIAN DAN HASIL BELAJAR SISWA KELAS XI IPA MAN 2 LUBUKLINGGAU - Ramadhan Fitri Yani; Wahyu Arini; Yaspin Yolanda (Jurnal Perspektif Pendidikan, 2023)
The purpose of this development research is to (1) increase learning independence and (2) improve students' physics learning outcomes after participating in learning using the phyphox application-assisted sound wave e-module. This research is a development research with the ADDIE model. The subjects of this study were students of grade XI Science 1 MAN 2 Lubuklinggau. Data collection techniques are carried out in the form of validation sheets, learning independence questionnaires and learning outcomes tests. The validation obtained 0.82 material experts, media experts 0.85 and linguists 0.87. Thus, the phyphox application-assisted sound wave e-module is very feasible for use in the classroom. And the results of the analysis of increasing learning independence of 85% and the analysis of learning outcomes with questions that have pre-test and post-test learning results, obtained a Gain Score of 0.54 included in the medium category. . Based on the research data obtained, it can be concluded that the sound wave e-module assisted by the phyphox application can improve student independence and learning outcomes so that it can be used in learning activities.